PENGEMBANGAN BAHAN AJAR DIGITAL BERBENTUK LKPD INTERAKTIF BERBASIS LIVE WORKSHEET PADA MATERI BANGUN DATAR KELAS IV SEKOLAH DASAR - Siregar, Nurkhairunnisa; Abdiani, Nindia; Maisarah, Maisarah (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2025)
This study aims to develop a digital teaching material in the form of an interactive student worksheet (LKPD) based on Liveworksheet for fourth-grade elementary school students on the topic of plane shapes. The development of this teaching material is driven by the need for engaging, interactive, and accessible learning media, especially to support both online and blended learning environments. The method used in this study is the Research and Development (RD) method with the development model used, namely Thiagarajan or 4D. The Thiagarajan or 4D model consists of four development steps, namely: define, design, develop, and disseminate. The results obtained in product validation showed a score of 91.67% by material experts, 91.67% by teaching material experts, 94.44% by language experts, and the average score obtained was 92.59% stated as very valid so that it can be concluded that the teaching material in the form of interactive LPKP based on Live Worksheet is suitable for use and can be tested on fourth grade elementary school students. The development results show that the interactive LKPD based on Liveworksheet is declared very feasible based on the validation results of material experts, media experts, and limited trials on students. In addition, the use of this LKPD can increase student involvement in the learning process and help them understand the concepts of flat shapes more concretely and enjoyably. Thus, this digital teaching material can be an alternative solution in improving the quality of mathematics learning at the elementary school level.